Census of the population 1940 - Occupation - Brantgärde, Lennart (University of Gothenburg, 2013)
This data collection is divided into two subset. For each municipality and town there is information about total population within the principal occupational groups agriculture and subsidiary industry, industry and craft, transport, storage, communication and commerce, public service and independent professions, domestic work, and unspecified occupation and also about total number of professionally employed. For towns with more than 10 000 inhabitants there is a subset including information about total population and number of professionally employed within the principal occupational groups and also within subgroups of these principal groups.

För samtliga kommuner och städer finns uppgifter om totala folkmängden inom huvudgrupperna jordbruk med binäringar, industri och hantverk, samfärdsel och handel, allmän förvaltningstjänst och fria yrken, husligt arbete och ospecificerad verksamhet samt uppgift om antal yrkesverksam befolkning. För städer med mer än 10 000 invånare finns dessutom ett dataset med uppgifter om hela folkmängden och antalet yrkesutövare inom huvudgrupperna samt uppgifter om hela folkmängden och antalet yrkesutövare inom undergrupper till ovannämnda huvudgrupper.
Folkräkningen 1940 - Yrkesgrupper
Keywords: occupations; yrken; population; befolkning; census data; folkräkningsdata; rural population; landsbygdsbefolkning; urban population; stadsbefolkning; Censuses; Folkräkningar; Employment; Sysselsättning; HISTORY; HISTORIA; Work Sciences; Arbetslivsstudier; History; Historia